Studi Efek Lama Perendaman Edible Coating Pati Talas terhadap Mutu Fisikokimia Jeruk Siam Selama Penyimpanan - Annisatul Mawaddah (Fakultas Teknologi Pertanian, 2025)
Edible coating of taro starch is one of the methods that can be used to extend the shelf life of Siam citrus. The thin layer covering the surface of the fruit can improve its structure and reduce damage during storage. In the application of taro starch edible coating, the immersion time needs to be considered, since differences in immersion duration may affect the thickness of the coating. This study aims to determine the effect of immersion time for edible coating made from taro starch on the physical and chemical quality of Siam citrus during storage at room temperature. The method used in this study was a Completely Randomized Design (CRD) with two treatment factors: immersion time (30, 60, and 90 seconds) and storage duration (0, 4, 8, 12, and 16 days). The data were analyzed using two-way ANOVA followed by Duncan’s test. Each treatment was repeated three times, and the observed variables included weight loss, color, texture, moisture content, pH, and total soluble solids (TSS). The results showed that taro starch edible coating was able to maintain the physicochemical quality of Siam citrus during storage compared to the control. Meanwhile, the 60-second immersion treatment produced the lowest values during storage, with weight loss of 12.95%, texture of 8.29 kg/cm2, moisture content of 88.27%, pH of 4.10, and TSS of 22.17 °Brix. For color analysis, the 90-second immersion treatment resulted in the lowest values, with L = 46.09, a* = –10.22, and b* = 15.28. Based on statistical analysis, the 90-second immersion time was effective in maintaining the physicochemical quality of Siam citrus, although it was not significantly different from the 30- and 60- second treatments.
Entry oleh Arif 2026 Maret 25
Keywords: Edible coating; Siam citrus; Taro starch; Shelf life; Immersion